The Influence of Organizational Culture and Human Capital on Employee Performance by Mediating Organizational Climate - Muhammad Ridho Hafidzi; Margono Setiawan; Himmiyatul Amanah Jiwa Juwita (Politeknik Siber Cerdika Internasional, 2024)
This study was conducted to analyze the influence of organizational culture on employee performance and human capital on employee performance with organizational climate. as mediation. Employees totaling 196 people were respondents in this study using saturated sample techniques. Data collection methods using questionnaires and analyzed using Warp PLS. The results of this study show that organizational culture does not have a significant effect on employee performance, while human capital has a significant effect on employee performance. Furthermore, organizational climate mediates the relationship of organizational culture to full employee performance and organizational climate mediates human capital to employee performance partially.